Pengaruh Media, Temperatur Dan Waktu Perlakuan Annealing Pada Spesimen Standar ASTM D638 Type IV Menggunakan Filamen ST PLA - Subakti, Yulian; -, Hasdiansah; Kurniawan, Zaldy (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2021)
Fused Deposition Modeling (FDM) is a technique of 3D Printing machines that is popularly used to print products. The printed product certainly has the ideal tensile strength characteristics if it has a precise size and good shape according to the standard. One of the materials that can be processed in a 3D printing machine is ST PLA. Research in terms of tensile testing has been carried out on PLA/ABS materials. However, tensile testing with annealing process using ST PLA filament is still very rarely done. From these problems, it is necessary to research to obtain optimal process parameters on 3D printing machines, to obtain the highest tensile strength from the annealing process using ST PLA material. This research was conducted using a 3D printer DIY Prusa model with a printing area of ​​XYZ, 300 mm x 300 mm x 350 mm. The material used is ST PLA filament with a diameter of 1.75 mm in green. The process parameters in this research are layer thickness, nozzle temperature and flow rate. For annealing media use beach sand, coffee and wheat. The shape of the test specimen follows the ASTM D638 type IV standard. As for the design of the process parameters using the Taguchi L9 method (33). The process parameter values ​​that produce the highest tensile strength without annealing are layer thickness 0.3 mm, nozzle temperature 205oC, and flow rate 100%. The annealing process parameters that produce the highest tensile strength are annealing time of 15 minutes, oven temperature of 110oC, for annealing media using coffee.